USING INNOVATIVE TEACHING METHODS IN TEACHING THE LIFE AND WORK OF BOBORAKHIM MASHRAB (Universal International Scientific Journal, 2026)
This article discusses the role and importance of using innovative teaching methods in teaching the life and work of Boborahim Mashrab, a prominent representative of Uzbek classical literature, in secondary schools in developing students' independent, creative, and imaginative thinking skills, based on personal experience.
Keywords: Mashrab, Sufism, Ghazal, Divine Love, Interactive Method, Literature Lesson, Analysis.